The Positive Effect of Debate Inside the Social Studies Classroom - Poddany, John (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
For far too long social studies classrooms having been missing a key aspect to bring classroom participation into instruction. The social studies classroom has been teacher-centered with an abundance of text to read and comprehend with little focus on bringing the students experiences and thoughts into the discussion. The social studies classroom is one that needs to prepare students for their civic duties outside of the classroom. This process begins with the students being able to form thoughts and opinions about topics to communicate to others. The strategy of using discussion questions that can lead to debate will also lead students to have a higher level of participation leading to better comprehension.